Membrane Localization of Piezo1 in the Context of Its Role in the Regulation of Red Blood Cell Volume - Bojan Božič; Saša Svetina; Saša Svetina (Frontiers in Physiology, 2022)
Piezo1 is a membrane nonspecific cation channel involved in red blood cells (RBCs) in the regulation of their volume. Recently, it was shown that it is distributed on the RBC membrane in a nonuniform manner. Here it is shown that it is possible to interpret the lateral distribution of Piezo1 molecules on RBC membrane by the curvature dependent Piezo1—bilayer interaction which is the consequence of the mismatch between the intrinsic principal curvatures of the Piezo1 trimer and the principal curvatures of the membrane at Piezo1′s location but without its presence. This result supports the previously proposed model for the role of Piezo1 in the regulation of RBC volume.